Using Qualitative Data Analysis Software to Support Learning and Teaching of Research Practices - Kikooma, Julius (International Journal for Cross-Disciplinary Subjects in Education, 2012)
In many universities and research institutions in Africa, there is a sense of growing frustration among social science scholars on the continent regarding the lack of good materials available in (and from) their context for teaching qualitative methods that successfully blend technology and methodology. This paper reflects upon the challenges and opportunities for integrating qualitative data analysis software in methodology classes and the implication for preparing new qualitative researchers for future roles. large qualitative data sets, a lack in local support means that researchers-in-the-making do not get enough guide or practice in using technology. As Johnstone observed, this has the consequence that project design and software use are often tacked together in an inefficient way to the detriment of outcome [5].
Keywords: Qualitative Data; Software; Research Practices